Development of Teaching Materials of The Qur'an Hadith Through Quizizz Media for Students of Madrasah Tsanawiyah - Dian Nur Rohmawati; Mu’awanah Mu’awanah; Muniron Muniron (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2022)
Technological sophistication has an impact on the field of education. One of them is the change of printed teaching materials to be technology-based, such as the use of teaching materials through Quizizz media. This study aims to (1) describe the product development of al-Qur'an Hadith teaching materials through Quizizz media for class VIII Madrasah Tsanawiyah students and (2) find out the effectiveness of using Al-Qur'an Hadith teaching materials through Quizizz media for Class VIII Madrasah Tsanawiyah students. This research uses Research and Development (R&D) 4D model (Define, Design, Develop and Disseminate) by Thiagarajan, Semmel and Semmel. The results showed (1) the product developed was in the form of Al-Qur'an Hadith teaching materials through Quizizz media for class VIII Madrasah Tsanawiyah students, meeting the appropriate criteria based on the validation of material experts 78%, media experts 74% and learning experts 94% (2 ) The effectiveness of teaching materials is obtained from the calculation of the t-test on the three materials of the Qur'an Hadith. The results obtained thitung > ttabel = 3.995 > 0.678 on the material I read the Qur'an correctly. For the material for sharing infak and sedekah, the results obtained are thitung > ttabel = 3.177 > 0.678. Chapter Strengthen faith by sharing, the result of thitung > ttabel = 5.866 > 0.678. The use of Quizizz led to differences in student learning outcomes. It can be concluded, that the teaching materials of the Qur'an Hadith through the media Quizizz class VIII Madrasah Tsanawiyah are considered effective in the learning process.